Reformulation of Land Policy for the Resolution of Abandoned Land Issues in Urban Areas - Lily Kalyana; Widodo Budidarmo (Yayasan Cendekia Gagayunan Indonesia, 2025)
The problem of abandoned land in urban areas reflects the failure of equitable and sustainable agrarian governance. Despite the existence of legal frameworks such as the Basic Agrarian Law (UUPA), Government Regulation Number 20 of 2021 concerning the Regulation of the Utilization of Abandoned Land, and Presidential Regulation Number 62 of 2023 concerning the Acceleration of Agrarian Reform, the reality shows that the effectiveness of these regulations remains low, both at the normative and implementation levels. This article aims to analyze the urgency of reformulating land policy to address the problem of abandoned land in urban areas. This research employs a normative juridical method, combining a legislative and conceptual approach, to examine the ineffectiveness of existing positive law. The results indicate that the key issues lie in weak oversight, minimal synergy between the central and regional governments, and landowner resistance to redistribution. Furthermore, socio-economic factors reinforce the dominance of land as a commodity, rather than as a means of fulfilling basic community rights. Therefore, policy reformulation based on distributive justice and the social function of land is needed, including the development of a comprehensive agrarian reform law, digitizing the land system, and strengthening the role of civil society in policy oversight. This reformulation is expected to serve as a strategic instrument in achieving equitable access to land and fostering inclusive and equitable cities